Pemahaman Keaksaraan Awal Anak Kelompok B Di TK Aisyiyah Bustanul Athfal 23 Dengok - Putri, Rosalina Trisna; Ifadah, Ayunda Sayyidatul; Fatmawati, Fitri Ayu (Universitas Muhammadiyah Gresik, 2025)
Abstract The background of this research is based on the results of observations and interviews with the homeroom teacher, it is obtained data that in ABA 23 DENGOK Kindergarten, especially group B of 29 children, there are 4 children who do not know initial literacy properly, children are still often upside down in writing the letters b and d and upside down in write the numbers 1 2 3 4 5. Seeing this, the researcher wants to know how the initial literacy comprehension of group B children at TK Aisyiyah Bustanul Athfal 23 Dengok and wants to know what factors influence it. In the study of